(untitled) (Baghdad Science Journal, 2007)
A dose of ten grams of the roots and leaves of Nettle (Urtica dioica) dissolved in (200)ml of boiled water then covered for (10)min. was given to a sample of (15) patients attending to the herbal department of ministry of health complaining of malnutrition and low Hb(hemoglobin) concentration and PCV(packed cell volume) levels with absence of any other predisposing factors disease inorder to find the effects of these roots and leaves on Hb and PCV levels for different periods of time in relation to age and sex variations . The study have shown that this mixture has a high significant effect (p